Development of a Swimming Learning Model With a Play Approach to Elementary School Students - Nurdiansyah; Ramadhan Arifin; Abdul Hakim Siregar; Hasyim; Ramadhani (UNIB Press, 2023)
The purpose of this study was to develop learning freestyle swimming for elementary school students, as well as to find out the effectiveness of the model that had been developed. The method in this study was to develop a freestyle swimming learning model for elementary school students using the Research & Development model approach from Brog and Gall. The aim of this research is to develop a swimming learning model for students at State Elementary School 1 Lokatabat Utara, State Elementary School Guntung Manggis, State Elementary School Landasan Ulin Utara. The small group trial consisted of 20 people while the large group trial consisted of 110 people. Data collection in this study was to review various literature or literature studies related to the model concepts that would be developed according to the product to be made and referred to needs analysis, expert review and field trials. To calculate the effectiveness test using (t-test) with an analysis of the difference between the two means for dependent samples. The results of the study of the freestyle swimming learning model for elementary school students are in accordance with the characteristics of the students and are effective for improving freestyle swimming learning.